(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the current evolving digital economy in the world, its advantages, factors of development and the favorable conditions created by the digital economy. Blockchain technology will also be considered in the development of the digital economy.